Islamophobia as a religious-based horizontal conflict and its resolution - Rodon Pedrason; Waluyo Handoko; Paulus Israwan Setyoko; Denok Kurniasih (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
Islamophobia is a complex issue to discuss, starting from history, to the terrorist and extremist acts behind it. The definition of the term Islamophobia itself is studied to look at this issue from the point of view of conflict with two perspectives of perpetrators and victims as well. This also includes the influence of the media in herding opinions and disseminating them, as well as the Islamophobia Resolution established by the United Nations as an effort to counter this anti-Islamic sentiment. Islamophobia is included in the category of a dangerous circle where if the chain is not immediately broken, discrimination will continue to occur, leading to violence that results in victims. Alignment between racism and Islamophobia is also important in order to build a narrative that both views are prohibited. There is no single solution to combat Islamophobia, but several efforts can be made to build awareness and integrate Islamic values with universal humanity values, and the Islamophobia Resolution is one of the initiatives for that.